Non-invasive Computational Techniques for Diagnosing Myocardial Ischemia: Challenges and Future of FFRCT/iFRCT - Bao Li; Jincheng Liu; Yang Yang; Hao Sun; Chi Zhu; Leo Hwa Liang; Zijie Wang; Luyao Fan; Suqin Huang; Xueke Li; Guangfei Li; Liyuan Zhang; et al. (Annals of Biomedical Engineering, 2026)

Climate-sensitive environmental drivers shaping epipelagic and mesopelagic fauna biodiversity patterns in the Amundsen–Bellingshausen Seas, Southern Ocean - Jiayu Fan; Yang Liu; Yanping Luo; Yuru Li; Mi Duan; Chunlin Liu; Zhenjiang Ye; Jianchao Li; Peng Sun; Chi Zhang; Jun Zhao; Jianfeng He; et al. (Environmental Research, 2026)

Railway CORS GNSS PWV forecasting using normal time-frequency transform and deep learning with transfer learning strategy - Chen Chang; Yanping Liu; Yong Wang; Yunlong Zhang; Xiangshun Meng; Haozhe Chi; Chunrui He (Advances in Space Research, 2026)

The atmospheric residual error model of time-series InSAR based on ERA-5 PWV in Beijing, China - Haozhe Chi; Yong Wang; Yunlong Zhang; Chengwu Yang; Chen Chang; Fei Qiao; Xiangshun Meng; Chunhong Liu; Yanping Liu (Advances in Space Research, 2026)

Preparation and characterization of gelatin/bacterial nanofibrillated cellulose composite membranes based on an ecological engineering strategy - Fengge Yu; Jieying Fan; Jialin Zhang; Xiangying Liu; Yue Meng; Yanping Chi; Zhiqiang Yang; Caiming Li; Hongrui Sun; Hua Zhang; Lining Kang (Food Hydrocolloids, 2026)

Balancing Accuracy and Speed: Improved D-FINE for Real-Time Ocean Internal Wave Detection - Lu Yu; Yanping Tian; Jie Chen; Cheng Chi; Tingting Li; Jianwei Li (Journal of Marine Science and Engineering, 2026)
Ocean internal waves (IWs), induced by density stratification and fluid perturbations, are significant oceanic phenomena prevalent across global oceans, profoundly impacting marine environments and engineering safety. Although one-stage object detection models are favored in practical applications due to their efficient inference, they often suffer from insufficient accuracy in IW detection tasks. To address this, we introduce a novel one-stage, anchor-free detection approach based on Transformer for IW detection, proposing a new algorithm named IW-D-FINE, which balances detection accuracy and inference efficiency. On the public SAR dataset, IW-D-FINE achieves an AP@0.5 of 90.5, significantly outperforming existing one-stage methods while maintaining faster inference speeds than mainstream two-stage models. Furthermore, to mitigate the scarcity of internal wave samples, we construct a small-scale IWs dataset, YH3-IW-2025, and validate the algorithm thoroughly on this dataset. Experimental results demonstrate that IW-D-FINE exhibits robust performance under complex background interference, highlighting its application potential and scalability in IW detection tasks.

Analysis of atmospheric residual error and construction of correction model for GACOS-Corrected PS+DS time-series InSAR based on ERA5 PWV - Fei Qiao; Yong Wang; Yunlong Zhang; Chen Chang; Haozhe Chi; Chunhong Liu; Xiangshun Meng; Yanping Liu; Chengwu Yang (International Journal of Remote Sensing, 2026)

Research on hourly precipitation prediction along railways based on ERA5 reanalysis and post-processing correction - Xiangshun Meng; Yong Wang; Yunlong Zhang; Chengwu Yang; Chen Chang; Haozhe Chi; Yanping Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Polysaccharides from Actinidia Lindl.: Extraction, bioactivities, and emerging applications in food and pharmaceutical industries - Lihao Wang; Chenqing Dong; Qian Wang; Chi Teng; Wuyou Gao; Yujia He; Jun Liang; Yonggang Xia; Haixue Kuang; Yanping Sun (Trends in Food Science & Technology, 2025)

Corrosion characteristics of low-carbon cast steel ZG230-450 in chloride-sulfate atmospheric environment - Xuan Zheng; Yanping Zhao; Hongxin Yang; Baorong Liu; Chi Zhang (Environmental Science and Pollution Research, 2025)

Microtopography-induced hydrological heterogeneity promotes the co-assembly of vascular plant and biocrust communities, providing synergistic protective functions for the Great Wall - Yanping Liu; Wanfu Wang; Jing Ren; Yanhong Gao; Fasi Wu; Yafei Shi; Hongtao Zhan; Chengxu Chi; Rongliang Jia (Science of The Total Environment, 2025)

Long-term and seasonal evaluation on environmental microbiology and water quality of Shanmei reservoir in southeast China - Jiamin Chang; Shanshan Zhang; Yanping Zhong; Siqi Ding; Wenzhou Zhang; Qiansheng Huang; Shouping Ji; Yulang Chi (Environmental Pollution, 2025)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

The feeding strategies of the antarctic lanternfish electrona antarctica (pisces: myctophidae) in the amundsen and cosmonaut seas (southern ocean), assessed with a classification tree analysis - Mi Duan; Chi Zhang; Yanping Luo; Libao Gao; Guankui Liu; Chunlin Liu; Yongming Sun; Jianchao Li; Shuyang Ma; Wenchao Zhang; Yongjun Tian (Polar Biology, 2024)

One-step self-assembly of multilayer graphene oxide via streamlined click reactions for sensitive colorimetric assays - Yanfeng Gao; Yanping Wang; Xinli Liu; Zhenxing Zhu; Zhun Li; Zhibin Zhang; Yi Yin; William Chi Shing Cho; Yujun Song; Yuzhen Wang (Analytica Chimica Acta, 2023)

Long-term variation of storm surge-associated waves in the Bohai Sea - Yanping Wang; Yongling Liu; Xinyan Mao; Yutao Chi; Wensheng Jiang (Journal of Oceanology and Limnology, 2019)

Position and Angular Misalignment Analysis for Implantable Wireless Power Transfer System Based on Magnetic Resonance - Fei-Xiang Gong; Zhiqiang Wei; Haokun Chi; Bo Yin; Ying Sun; Yanping Cong; Mingui Sun (Journal of Medical and Biological Engineering, 2017)